The Effect of Alpha-galactosidase Enzyme with and Without Avizyme 1502 on Performance of Broilers Fed Diets Based on Corn and Soybean Meal - Waldroup, P.W.; Fritts, C.A.; Keen, C.A.; Yan, F. (International Journal of Poultry Science, 2005)
One experiment in wire-floored batteries and two experiments in litter-floor pens were conducted to evaluate the effects of addition of alpha-galactosidase enzyme to typical corn-soybean meal based diets for broilers. In two experiments, Avizyme 1502 was fed in conjunction with the alpha-galactosidase enzyme. In formulating test diets, soybean meal was assigned an ME value beginning at 2440 ME kcal/kg and increased on the assumption that the addition of the enzyme would increase the ME of soybean meal by 10, 20, or 30%. In two experiments, the level of supplemental poultry oil remained constant with increases in apparent ME, while in the third the level of supplemental poultry oil was reduced as the assumed ME level of soybean meal was increased. Male chicks of a commercial broiler strain were used in all experiments. Overall, the results of the three experiments suggest little if any improvement in metabolizable energy of SBM as a result of the addition of an exogenous alpha-galactosidase enzyme, as indicated by evaluation of body weight gain, feed utilization, calorie conversion, or mortality. No improvements in the above parameters were noted when Avizyme 1502 was added to the diet, alone or in combination with the alpha-galactosidase enzyme. At the present time, it does not appear that diets based on corn and SBM of average quality would benefit from supplementation with these enzymes.